1989
DOI: 10.1007/bf00442012
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic and opioidergic influences on the antinociceptive effect of clomipramine in the formalin test in rats

Abstract: Although tricyclic antidepressants are especially useful in the treatment of chronic pain conditions, most of the work about its mechanism of action has been made on acute pain tests. The present study was aimed at studying the role played by noradrenergic and opioidergic influences on the antinociceptive activity of subchronically administered clomipramine in the formalin test (a tonic pain model) in rats. Clomipramine produced antinociception after 7 days, administration (2.5 mg/kg/day), an effect equivalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 26 publications
2
12
0
1
Order By: Relevance
“…Many studies have reported the inhibition of antinociceptive effect of ADs by naloxone but exclusively after acute (Michael-Titus and Costentin, 1987;Ardid and Guilbaud, 1992;Valverde et al, 1994;Gray et al, 1998) or daily and twice daily administrations (Ansuategui et al, 1989) in different pain tests and models. The total inhibition of the effect demonstrates that CMI needs a functional opioid system to induce its antihyperalgesic effect in conditions of repeated treatment in a model of neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the inhibition of antinociceptive effect of ADs by naloxone but exclusively after acute (Michael-Titus and Costentin, 1987;Ardid and Guilbaud, 1992;Valverde et al, 1994;Gray et al, 1998) or daily and twice daily administrations (Ansuategui et al, 1989) in different pain tests and models. The total inhibition of the effect demonstrates that CMI needs a functional opioid system to induce its antihyperalgesic effect in conditions of repeated treatment in a model of neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this enhanced antinociceptive effect was replicated with the selective serotonin uptake inhibitor fluoxetine, but not with dopamine or norepinephrine transporter inhibitors, suggesting that the effect depended on serotonin transporter inhibition (Gatch et al, 1998). Clomipramine has also been shown to enhance the antinociceptive effects of morphine in rodents (Kellstein et al, 1984;Ansuategui et al, 1989;Sierralta et al, 1995). Overall, these studies suggest further research on mu agonist and serotonin uptake inhibitor drug mixtures as candidate analgesics is warranted.…”
Section: Introductionmentioning
confidence: 93%
“…In contrast, coadministration of either doxepin or venlafaxine with morphine made it less effective in attenuation of neuropathic pain symptoms. The analgesic action of antidepressants after local administration deserves further study due to the first and only experimental and clinical data that focused on the analgesic efficacy of antidepressants after different methods of administration (oral, subcutaneous, intraperitoneal, intrathecal, topical) in different models of pain [9,15,[35][36][37][38]. The analgesic effect of antidepressants is different from their action as a mood elevator.…”
Section: Discussionmentioning
confidence: 99%